Rewriting Marpole : the path to cultural complexity in the Gulf of Georgia - Clark, Terence N. (Mercury series., 2013)
A prehistoric culture study of a key area on the Canadian northwest coast. This book examines prehistoric culture change in the Gulf of Georgia region of the northwest coast of North America during the Locarno Beach (3500–1100 BP) and Marpole (2000–1100 BP) periods. The Marpole culture has traditionally been seen to possess all the traits associated with complex hunter-gatherers on the northwest coast (hereditary inequality, multi-family housing, storage-based economies, resource ownership, wealth accumulation, etc.) while the Locarno Beach culture has not. This research examined artifact and faunal assemblages as well as data for art and mortuary architecture from a total of 164 Gulf of Georgia archaeological site components. Geographic location and ethnographic language distribution were also compared to the archaeological data. Analysis was undertaken using Integrative Distance Analysis (IDA), a statistical model developed in the course of this research. Results indicated that Marpole culture was not a regional phenomenon, but much more spatially and temporally discrete than previously thought.